STATING AND DEFENDING NEW KNOWLEDGE CLAIM: A RHETORICAL ANALYSIS ON THE DISCUSSION SECTION OF ENGLISH MASTER THESIS BY INDONESIAN EFL LEARNERS - Warsito Warsito; safnil arsyad; Alamsyah Harahap (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT The discussion section is considered the most important section of a thesis but also the most difficult to write especially by university students. This study investigated the move-step and rhetorical pattern of discussion section in 20 English Master Theses written by Indonesian EFL postgraduate students. Following the model suggested by Loan and Pramoolsook (2015), this study found that students constructed the discussion section according to their perceived communicative purposes of discussion section. The most noticeable feature of the section is the occurrence of Move 2 (reporting results) and Move 4 (Commenting on results) occurring in all texts making them obligatory moves. In terms of step, interpreting results and referring to other studies in Move 4 are also considered as obligatory steps. The findings of this study are useful particularly for EFL students; that is to facilitate them to better understand the rhetorical structure of thesis discussion section when written in English. ABSTRAK Bagian pembahasan dianggap sebagai bagian yang paling penting dalam tesis tetapi juga yang paling sulit ditulis terutama oleh mahasiswa atau penulis baru. Penelitian ini penting untuk menyelidiki pola retorika bagian pembahasan tesis mahasiswa magister bahasa Inggris yang ditulis oleh mahasiswa Indonesia. Mengikuti model yang disarankan oleh Loan and Pramoolsook (2015), penelitian ini menemukan bahwa mahasiswa mengorganisir bagian pembahasan sesuai dengan tujuan komunikatif yang mereka anggap penting. Tujuan komunikatif yang paling menonjol dari bagian ini adalah ‘Move’ 2 (tahapan melaporkan hasil peneitian) dan ‘Move’ 4 (tahapan mengomentari hasil penelitian) yang ditemukan di semua teks sehingga dianggap wajib. Dalam hal langkah (Steps), langkah menafsirkan hasil penelitian dan langkah mengacu pada penelitian terdahuluan dalam ‘Move’ 4 dianggap sebagai langkah wajib. Temuan penelitian ini berguna terutama untuk mahasiswa magister bahasa Inggris, yaitu untuk memudahkan mereka memahami struktur retorika dari bagian pembahasan tesis yang ditulis dalam bahasa Inggris. How to Cite: Wasito., Syah, S. A., Harahap, A. (2017). Stating and Defending New Knowledge Claim: a Rhetorical Analysis on the Discussion Section of English Master Thesis by Indonesian EFL Learners. IJEE (Indonesian Journal of English Education), 4(2), 188-207. doi:10.15408/ijee.v4i2.6746